Dyslexia : a parents' and teachers' guide - Payne, Trevor, 1948- (Parents' and teachers' guides ;, 1999)
"This book is a handy, practical guide to the educational difficulties encountered by children experiencing specific learning difficulties (dyslexia). It is aimed at parents of dyslexic children and non-specialist teachers who have these children in their classes. It is written by two experienced and qualified practitioners. The authors have aimed to write the book in plain English, with a minimum of jargon and technical language."--Jacket